2020
DOI: 10.1136/bmjdrc-2019-000947
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal obesity and hypertension are correlated with health-related quality of life in Taiwanese adults with metabolic syndrome

Abstract: ObjectiveMetabolic syndrome (MetS) gains more attention due to high prevalence of obesity, diabetes and hypertension among adults. Although obesity, diabetes and hypertension can certainly compromise health-related quality of life (HRQoL), the correlations of sociodemographic factors, quality of life and MetS remains unclear. This study aims to investigate the association between HRQoL and MetS in an Asian community of the sociodemographic characteristics.Research design and methodsWe performed a cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…A recent study conducted in Colombia by Mendoza-Romero et al showed that low socioeconomic status, measured as level of education, was associated with poorer self-perceived health in women [ 55 ]. The findings of the present study with regard to obesity as a factor for poor self-perceived health, especially in women with low level of education, are in keeping with previous research [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
“…A recent study conducted in Colombia by Mendoza-Romero et al showed that low socioeconomic status, measured as level of education, was associated with poorer self-perceived health in women [ 55 ]. The findings of the present study with regard to obesity as a factor for poor self-perceived health, especially in women with low level of education, are in keeping with previous research [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
“…It was reported widely that presence of metabolic syndrome including diabetes mellitus, obesity and hypertension had a negative influence on HRQoL in various populations [ 27 , 28 ]. However, one previous study differed in terms of showing a similar association [ 29 ].…”
Section: Discussionmentioning
confidence: 94%
“…While inverse trends in subgroups remained in these two populations, the differences in the associations between HbEO and the prevalence of abdominal obesity in hypertension and overall obesity in diabetes are consistent with these associations previously reported. Previous studies in patients with type 2 diabetes mellitus have demonstrated the phenomenon of the obesity paradox whereby higher BMI in the overweight population is associated with a lower risk of mortality ( 37 ), and patients with HTN are often associated with abdominal obesity due to the lipo-metabolism abnormalities ( 38 , 39 ), which suggested that there might be a common pathway and metabolism disturbance to chronic exposure of EO, while EO exposure through smoking is the major resource in the general population and adult tobacco smokers tend to have lower BMIs and unhealthier diets relative to nonsmokers due to the increased insulin resistance, central fat accumulation, and aberrant lipolysis ( 1 , 40 , 41 ). Although the inverse trend remained in the smoking group, which is in line with our understanding, the current results did not differ between smokers and nonsmokers in the subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%